2005
DOI: 10.1007/s10344-005-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoptes scabei var. wombati infection in the common wombat (Vombatus ursinus)

Abstract: Sarcoptic mange has been identified as the most significant infectious disease affecting the common wombat (Vombatus ursinus). Biochemistry and haematology values for wild common wombats have not been published previously. A 35% of the wombat population were exhibiting clinical signs of the disease. Significant changes in blood haematology and biochemistry parameters were observed in affected animals. A seasonal variation in numbers of animals affected was demonstrated. Females appeared to be more commonly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 8 publications
3
40
1
Order By: Relevance
“…This result concurs with the fact that severely diseased SHNW at the study site were, on average, 9.9 kg lighter than healthy wombats (Ruykys et al, 2009). Decreases in creatinine have also been noted in mangy coyotes (Canis latrans; Pence et al, 1983), European rabbits (Arlian, 1989), and common wombats (Hartley and English, 2005).…”
Section: Clinical Pathologysupporting
confidence: 75%
See 4 more Smart Citations
“…This result concurs with the fact that severely diseased SHNW at the study site were, on average, 9.9 kg lighter than healthy wombats (Ruykys et al, 2009). Decreases in creatinine have also been noted in mangy coyotes (Canis latrans; Pence et al, 1983), European rabbits (Arlian, 1989), and common wombats (Hartley and English, 2005).…”
Section: Clinical Pathologysupporting
confidence: 75%
“…Similarly, lymphocytosis is associated with chronic infection (Clark, 2004), and the rise observed in diseased SHNW concurs with results for mange-infected humans (Morsy and Gaafar, 1989), dogs (Arlian et al, 1997), and cattle (Lö wenstein et al, 1996). In contrast, Skerratt et al (1999) and Hartley and English (2005) found that mangy common wombats had lower lymphocyte values than did healthy animals. Other stressors or variation in infection severity, extent, and duration may explain the discrepancy between the two species.…”
Section: Clinical Pathologymentioning
confidence: 93%
See 3 more Smart Citations